Does the expansion of higher education increase the equality of educational opportunities? Evidence from Italy - Massimiliano Bratti; Daniele Checchi; Guido de Blasio (Institute for the Study of Labor (IZA), 2008)
This paper studies the role of the expansion of higher education (HE) in increasing the equality of tertiary education opportunities. It examines Italy's experience during the 1990s, when policy changes prompted HE institutions to offer a wider range of degrees and to open new sites in neighbouring provinces. Our analysis focuses on non-mature full-time students and the results suggest that the expansion might have had only limited effects in terms of reducing existing individual inequality in HE achievement as the greater availability of courses had a significantly positive impact only on the probability of university enrolment but not on that of obtaining a university degree.
Keywords: I2; 370; Family background; higher education; Italy; Hochschulpolitik; Bildungschancen; Familiensoziologie; Wirkungsanalyse; Bildungsniveau; Italien